Flight and landing activity of Rhopalosiphum maidis (Homoptera: Aphididae) in bean monocultures and beancorn mixtures - Bottenberg, H.; Irwin, M.E. (Georgia Entomological Society, 1992)
Rhopalosiphum maidis (Fitch) dominated the aerial aphid plankton in bean (Phaseolus vulgaris L.) monocultures and mixed cultures of bean with corn (Zea mays L.) in Illinois. It was also the most common species landing on bean plants in this study during the summer of 1987. More flight activity was recorded in the monocultures than in the mixtures. More R. maidis flew at the top of the bean canopy than at the level of the corn canopy. Densely planted corn rows suppressed flight activity more than did sparsely planted rows. Plots that were planted early had lower aphid catches over the same time than did plots planted 13 and 24 days later. Aphid flight activity was negatively correlated with ground cover, corn barrier height, and corn barrier density. Aphid landing activity was not affected by planting date or corn row density but was negatively and significantly correlated with ground cover. Stepwise regression analysis revealed that ground cover was more important than barrier height and barrier density in suppressing flight and landing activity of R. maidis.